Analisis Hukum Perjanjian Dalam Transaksi E-Commerce: Tinjauan Terhadap Perlindungan Konsumen Berdasarkan Peraturan Perundang-Undangan - Hermanto, Dennis; Lie, Gunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Advances in information technology have changed the trading landscape with e-commerce transactions, offering convenience but at the same time posing consumer protection risks. This research mainly aims to examine the legal framework that governs agreements related to e-commerce transactions and consumer protection, as outlined by the applicable legal and regulatory provisions in Indonesia. This research method uses normative legal research methods, which apply legislative and conceptual approaches, as well as researching various legal sources such as the Civil Code, the Criminal Code, Law No. 8 of 1999 concerning Consumer Protection and the ITE Law. The findings of the study show that, although the existing legal framework provides an adequate foundation for consumer protection, there are still implementation challenges regarding consumer awareness, regulatory socialization, and dispute resolution mechanisms. Strengthening integration between traditional legal principles and specific rules for electronic transactions is essential to fostering a transparent, fair, and trustworthy digital commerce ecosystem.